Non-uniform muscle adaptations to eccentric exercise and the implications for training and sport - Hedayatpour, N.; Falla, D. (Journal of Electromyography and Kinesiology, 2012)
Due to the variations in morphological and architectural characteristics of fibers within a skeletal muscle, regions of a muscle may be differently affected by eccentric exercise. Although eccentric exercise may be beneficial for increasing muscle mass and can be beneficial for the treatment of tendinopathies, the non-uniform effect of eccentric exercise results in regional muscle damage and as a consequence, non-uniform changes in muscle activation. This regional muscle weakness can contribute to muscle strength imbalances and may potentially alter the load distribution on joint structures, increasing the risk of injury.